Test cuantitativo sensorial en dolor - Domingues B., Laura; Miranda M., Ana Luisa (Revista Hospital Clínico Universidad de Chile, 2015)
Pain is an unpleasant sensory and emotional experience, which is present in many diseases, and the central symptom of many of them. However, their diagnosis and evaluation methods have not changed much in the last century. Tools to quantitatively analyze this symptom and its underlying pathophysiological mechanisms are needed. The quantitative sensory test (QST) is a test done several decades ago for research purposes. However, in recent years, its use in different pain conditions have placed it as a tool to consider in evaluating a patient. The aim of this review is to provide information on the current performance of this test and its clinical applications development.